Surveillance in occupational contact dermatitis - Uter, Wolfgang (Kanerva's Occupational Dermatology, 2019)
Surveillance of occupational contact dermatitis addresses time trends and subgroups at risk. Preferably, surveillance should be based on robust, reliable, and valid classification systems both of morbidity and exposure(s). Moreover, surveillance needs to be detailed enough to be valuable, in particular concerning contact allergy to various defined substances (haptens). Data used for surveillance need a sufficient level of methodological standardization, e.g., for patch testing used to diagnose contact allergy. Internationally, a number of surveillance schemes for occupational diseases, including occupational skin diseases, have been implemented. These are described and discussed briefly in the present chapter. In addition to such on-going schemes, special projects provided some insights into the usefulness of the different methods used. Clinical surveillance of contact allergy, based on clinical and demographic as well as patch test data collected within (inter)national networks, can contribute to surveillance from another perspective, and usually with some more detail concerning causative allergens.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Contact allergy; Contact dermatitis; Epidemiology; Occupational; Surveillance